Optimization of Management Functions in Administrative Services at SMK Kartika XX-1 Makassar - Saputri, Ananda; Akib, Haedar; Saleh, Sirajuddin (ASHA Publishing, 2024)
The administrative management function refers to the set of activities and responsibilities required to ensure that school administration runs smoothly and efficiently. The main purpose of this study is to find out the application of management functions to administrative services at SMK Kartika XX-1 Makassar and to find out the supporting and inhibiting factors in optimizing administrative services at SMK Kartika XX-1 Makassar. This study uses a qualitative approach with a type of descriptive research that focuses on the application of management functions based on indicators of planning, organizing, directing, and supervising. The data collection techniques used are observation, interviews, and documentation. Based on the results of the study, it shows that the optimization of the management function in administrative services at SMK Kartika XX-1 Makassar can be said to be